Promotion of Perinatal Mental Health - Adhikari, Bhabani (NUTA Journal, 2018)
The aim of this paper is to discuss different aspects of perinatal mental health like; risk factor, impact, issues and to suggest the guidelines for promotion of perinatal mental health. Perinatal mental health is an emerging concept, generally refers to the period 22 completed weeks (i.e. 154 days) of gestation and ending seven completed days after birth. During the pregnancy women may suffer from different mental health problems such as anxiety and depression. Lack of nutritious food, proper healthy housing, and adequate time for rest, quality health services and positive support by the intimacy partner are major responsible factors for getting mental disorder during perinatal period. Problem with in-laws and domestic violence are also responsible for this. Individual, family, community and national agencies should aware the problem and difficulties of the perinatal period and ways to eliminating the associated problems by their action and efforts. Without waiting the sign and symptoms of depression all well pregnant women need to be screened as part of their perinatal health check.